Logical intuitions or matching heuristics? Examining the effect of deduction training on belief-based reasoning judgments. - Ghasemi, Omid; Handley, Simon J.; Stephens, Rachel G. (Memory & Cognition, 2025)
When individuals are asked to evaluate the believability of the conclusions to valid or invalid arguments, they often endorse valid conclusions at higher rates than invalid ones. This effect of validity on belief judgments—the "logic-belief effect" —is considered evidence of intuitive logic. However, recent studies challenged this interpretation by demonstrating that "pseudo-logical" arguments interfere with belief judgments in the same way as valid logical structures do. This finding suggests that a simple heuristic that relies on the matching of constituent propositions, rather than sensitivity to logical validity per se, may lead to the logic-belief effect. To further test this matching heuristic account, across two experiments, we instructed participants to evaluate the conclusions of a series of logical and pseudo-logical arguments based on logic or belief, before and after a logic training block. The results showed that whilst both judgment types were impacted by both logical and pseudo-logical structures before training, after training the effect of the latter was indeed minimized in logic judgments but not belief judgments. The results largely support the matching heuristic account, which have important implications for contemporary dual-process theories of reasoning.